Microplastic Type and Densityin the Coastal Area of the Apar Village, Pariaman, West Sumatera Province - Rova Erwinda Fitri; M.Fauzi M.Fauzi; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Microplastic is plastic pieces with size (≤ 5 mm).The presence of microplastic may negatively affects the organisms, as it may be swallowed and can not be digested properly. To understand the correlation of microplastic presence and macrozoobenthos density, a research has been conducted in May-June 2019. There were 3 sampling sites and there were 3 plots (50x50 cm) in each site. Sediment inside the plot was scrapped   10 cm depth. The sediment was then sieved (5 and 1 mm mesh size), dried and soaked in 35% NaCl. The floating microplastics were then collected and identified using a dissecting microscope.Results shown that there were 4 microplastic type present, they were fiber, film, foam, and fragment. The most microplastictype was found is fiber with density 1200 item/m3. The lowest microplastictype was found is foam with density 280 item/m3. The enviroment  quality parameters are as follows : water temperature was 30-32 oC, soil temperature was 33-35 oC, salinity was 29-30 ‰ and sediment fraction type is muddy sand.Keywords:Pollution Plastic,Intertidal Zone, Sediment, Fiber, Foam